KITAB RĀHATU ṢALIHIN WA ṢAWĀ ‘IQU AL-MUNAFIQĪN - Sobari, Dolla (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2018)
Sumatera stores many cultural works of ancestors, particularly those in the province of Bangka Belitung Islands. One of them is the book of Rāhatu Ṣālihin wa Ṣowā‘iqu Al-Munafiqīn which is a religious script written in Arabic language and has several overarching articles for the advancement of islamic religious knowladge this research examined the manuscript in depth. This study revealed that the manuscript contains wich information about the articles conveering with worship procedures for muslim. Method of philology was used in the research by applying steps such as inventory of manuscript, description of manuscript, editing of manuscript, text translation and analysis of the manuscript contents.